Creative therapies with traumatized children - Bannister, Anne (Jessica Kingsley, 2003)
As a probation officer and social worker, Anne Bannister has successfully used creative therapies with abused children for 25 years. Combining her practical experience and recent doctoral research she reflects on how and why these therapies actually work in the healing process. She shows how in 'the space between' children and their therapists, the child and adult can each use their creative skills to aid developmental processes, reverse negative brain patterns and affect positive behavioural changes to heal the damage caused by severe abuse in childhood. The author presents a practical model.